(untitled) (Research, Society and Development, 2022)
Objective: To identify the factors that interfere in the safety of surgical patients related to identification in the Neurosurgery unit. Methodology: This is a quantitative, exploratory study. It was carried out in a University Hospital of Rio de Janeiro, and the target population were nurses and nursing technicians, who performed their work activities in the Neurosurgery unit. The activities of the professionals were observed, contemplating the objectives of identification according to the Patient Safety Standards, concomitantly, a questionnaire with closed questions was applied to understand the professionals’ understanding of identification. Data analysis was non probabilistic, using descriptive statistics, using Stata release11 and BioEstat. Results: The knowledge about patient safety reported by nursing professionals presents significant differences when comparing the activities performed regarding patient identification and work activities, such as divergence regarding wristband conference and patient identification data; non-administration of the medication at the correct time and lack of guidance. Conclusion: It was found the need to seek improvements in the patient identification process, especially regarding professional conduct, understanding that the actions performed in the hospital environment can make safety protocols more effective.